Discovery of a Novel Hybrid of Vorinostat and Riluzole as a Potent Antitumor Agent - Xu, Qifu; Liu, Chunxi; Zang, Jie; Gao, Shuai; Chou, C. James; Zhang, Yingjie (Frontiers in Cell and Developmental Biology, 2020)
Vorinostat (suberoylanilide hydroxamic acid, SAHA) is the first approved histone deacetylase inhibitor (HDACI), a group of validated cancer therapeutic agents targeting epigenetics. Riluzole is a medication used to treat amyotrophic lateral sclerosis (ALS), the antitumor potency of which has been recently revealed. Herein, a novel hybrid of vorinostat and riluzole (compound 1) was rationally designed, synthesized and evaluated. Compared with vorinostat, compound 1 exhibited superior total HDAC inhibitory activity and similar HDAC isoform selective profiles. The intracellular HDAC inhibition of compound 1 was confirmed by Western blot analysis. Moreover, compound 1 possessed more potent in vitro antiproliferative activity against all tested solid and hematological tumor cell lines than vorinostat. In vitro metabolic stability evaluation revealed the better human plasma stability and comparable human liver microsomal stability of compound 1 relative to vorinostat. Additionally, compound 1 demonstrated more significant in vivo antitumor activity in a MDA-MB-231 xenograft model than vorinostat, which could be attributed to its superior in vitro antiproliferative activity and metabolic stability. Taken together, the results presented here support further research and development of compound 1 as a promising antitumor agent.